Synthesis, Crystal Structure and Characterization of Zn(II) Complex Constructed from 2,2’-Bisbenzimidazole - Yang, Yan; Li, Chang-Gui; Luo, Xu-Jian; Luo, Zhi-Hui; Liu, Rong-Jun; Jiang, Yue-Xiu; Liang, Wei-Jiang (Asian Journal of Chemistry, 2014)
A new complex associated with Zn ion, [Zn(OH-H2Bdc)(Bibim)]n (1), (OH-H2Bdc = 5-hydroxyisophthalic acid, Bibim = 2,2'-bisbenzimidazole) has been synthesized under hydrothermal conditions and characterized by elemental analysis, FT-IR spectroscopy, TG/DTG and fluorescence spectra. X-ray crystallographic studies reveal that complex [Zn(OH-H2Bdc)(Bibim)]n (1) crystallizes in a monoclinic space group P21/n, each Zn atom is five-coordinated and adopts a distorted square-pyramidal coordination environment. There exists a 2-D supramolecular network linked by hydrogen bonds and face-to-face p-p interactions between adjacent benzene rings (3.768 Å) and imidazole rings (3.742 Å). A three-dimensional supramolecular network is further constructed through p-p stacking and hydrogen-bonding interactions between the helices. The TG/DTG shows that it collapsed with total loss of 84.8 (calc. 86.3 %). Blue fluorescent emission of the complex was determined at 506 nm in the solid state.